Variability in yield and phytochemicals content in mandukapanri (Centella asiatica) as influenced by nutrient management - JAT, R S; GAJBHIYE, N A (The Indian Journal of Agricultural Sciences, 2016)
A two years field experiment was conducted to study the influence of nutrient management on herbage yield, triterpenes content and their correlation with NPK, triterpenes yield, and NPK content and their use efficiencies in Centella asiatica (L.) Urban. Results indicated that application of FYM 15 tonnes/ha and NPK 60:50:60 at planting and NK 60:60 kg/ha at 5th harvest as basal along with N 20 kg/ha as split application at each harvest recorded highest dry herbage yield. The asiaticoside (AS) and madecassoside (MS) content increased with FYM application, whereas, decreased with NPK, however, asiatic acid (AA) and madecassic acid (MA) content markedly increased with FYM and NPK both. Highly strong relationships were exhibited between plant NPK content with AA and MA content. Triterpenes yield was recorded highest with the application of FYM 15 tonnes/ha and NPK 60:50:60 at planting and NK 60:60 kg/ha at 5th harvest as basal along with N 20 kg/ha as split application at each harvest. Application of FYM and NPK significantly influenced N and K content and their agronomic and use efficiencies, whereas, P content and it’s agronomic and use efficiency were significant with NPK and non-significant with FYM. Thus, application of FYM 15 tonnes/ha and NPK 60:50:60 at planting and NK 60:60 kg/ha at 5th harvest as basal along with N 20 kg/ha as split application at each harvest found optimum to harvest maximum herbage and triterpenes yield and to produce quality raw drugs of C. asiatica.